Market imperfections, skills and total factor productivity: Firm-level evidence on Belgium and the Netherlands - Sabien Dobbelaere; Mark Vancauteren (National Bank of Belgium, 2014)
This paper revisits the relationship between competition and total factor productivity by analyzing how the type and the degree of product and labor market imperfections aect dierent moments of total factor productivity distributions. Following the methodology developed in Dobbelaere and Mairesse (2013), we use an unbalanced panel of 5,285 ?rms over the period 2003-2011 in Belgium and 9,653 ?rms over the period 1999-2008 in the Netherlands to ?rst classify 30 comparable manufacturing and service industries in 6 distinct regimes that dier in the type of competition prevailing in product and labor markets. In both countries, the dominant regime is one of imperfect competition in the product market and e cient bargaining in the labor market. We ?nd important cross-country differences in the composition of industries making up the regimes and cross-country variation in the levels of product and labor market imperfection parameters within the dominant regime. We then provide clear descriptive evidence of total factor productivity distributional characteristics varying by the type of competition predominating in product and labor markets and to some extent by the degree of product and labor market imperfections. In both countries, average total factor productivity growth rates are found to be higher in high-skilled enterprises in all regimes, except for the regime characterized by perfect competition in both markets.
Keywords: C23; D24; J50; L13; 330; Rent sharing; monopsony; price-cost mark-ups; human capital; total factor productivity; panel data; Unvollkommener Markt; Produktivitätsentwicklung; Industrie; Dienstleistungssektor; Monopson; Humankapital; Schätzung; Belgien; Niederlande